The effective English language teacher from the perspective of Ecuadorian university students - Daysi Narváez-Cantos (Maskana, 2022)
Studying EFL teacher effectiveness has been a constant issue in the last decade. These investigations focused on teachers’ and education administrators’ perceptions. Most of them were conducted in countries different from Latin America. This research aimed to create a profile of university students’ perceptions concerning the qualities of an effective EFL teacher. For doing so, a quantitative approach was used involving the application of the Effective English Language Teacher (EELT) questionnaire of Roya Zamani & Ahangari (2016) to learners from a public university (N=324). The findings revealed that the participants value pedagogical knowledge as the most relevant dimension of an effective EFL university teacher above organization and communication skills, socio-affective skills, and English proficiency. According to the surveyed student population, the three main relevant features of an effective EFL university teacher are being flexible with grading (1.70), having a good sense of humor (1.65), and avoiding direct criticism of students when they make errors (1.61). The article concludes by outlining some recommendations.